Circadian Clock Genes in the Metabolism of Non-alcoholic Fatty Liver Disease - Shi, Dongmei; Chen, Jie; Wang, Jiaofeng; Yao, Jianfeng; Huang, Yiqin; Zhang, Gansheng; Bao, Zhijun (Frontiers in Physiology, 2019)
Non-alcoholic fatty liver disease (NAFLD) is a common disease, which is characterized by the accumulation of triglycerides in the hepatocytes without excess alcohol intake. Circadian rhythms can participate in lipid, glucose, and cholesterol metabolism and are closely related to metabolism seen in this disease. Circadian clock genes can modulate liver lipid metabolism. Desynchrony of circadian rhythms and the influences imparted by external environmental stimuli can increase morbidity. By contrast, synchronizing circadian rhythms can help to alleviate the metabolic disturbance seen in NAFLD. In this review, we have discussed the current research connections that exist between the circadian clock and the metabolism of NAFLD, and we have specifically focused on the key circadian clock genes, Bmal1, Clock, Rev-Erbs, Rors, Pers, Crys, Nocturnin and DECs.